2006
DOI: 10.1007/s00264-006-0181-0
|View full text |Cite
|
Sign up to set email alerts
|

Distraction osteogenesis for ulnar lengthening in Kienbock’s disease

Abstract: Ulnar lengthening is an accepted modality of treatment to achieve joint levelling in Kienbock's disease. The conventional method of ulnar lengthening with a plate and bone graft is fraught with complications including graft site morbidity, non-union, hardware removal and difficulty in the achievement of a proper length. We used a Umex distractor to achieve distraction osteogenesis in a group of 12 patients and assessed them over an average follow-up period of 29.5 months. We had one excellent, ten good and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
2
5
0
1
Order By: Relevance
“…8 Negative ulnar variance has been postulated to be more predisposing to this disease. 9 Nine patients (81.2%) in this study had a negative ulnar variance. The treatment depends on the staging of the disease and the aim is to provide acceptable wrist function with no pain by decompressing the forces across lunate.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…8 Negative ulnar variance has been postulated to be more predisposing to this disease. 9 Nine patients (81.2%) in this study had a negative ulnar variance. The treatment depends on the staging of the disease and the aim is to provide acceptable wrist function with no pain by decompressing the forces across lunate.…”
Section: Discussionmentioning
confidence: 62%
“…10 It has been shown that even if there is no radiological arthrosis, arthroscopically both radioscaphoid and capitolunate joints have shown joint damage, hence joint levelling procedures, as well as proximal row carpectomy, was not thought to be suitable and limited intercarpal arthrodesis was advised. 9 Furthermore, there have been no comparative studies, randomized or nonrandomized, which prove the superiority of any one procedure over the other. The outcomes of both joint levelling, as well as limited arthrodesis, in various studies are presented in ►Tables 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…The goals for treatment include pain relief, motion preservation, and maintenance of strength and function, 16 although there is insufficient evidence supporting the superiority of any single treatment procedure that can consistently and reliably achieve these goals. 17 Additionally, there is a lack of level 1 evidence from large, prospective, randomized trials comparing different treatment options for Kienböck disease, as this is a rare disease making it difficult to obtain enough power to obtain statistically significant results [18][19][20][21][22][23][24][25][26][27][28][29][30][31] ; thus, the aim of this study was to determine the current trends and common practices by hand surgeons for the treatment of Kienböck disease at different Lichtman stages.…”
mentioning
confidence: 99%
“…A new universal micro external fixator system (UMEX TM ) has been introduced in human medicine to treat delicate orthopaedic conditions (26). The UMEX system is available in a smaller (alpha) and a larger (beta) clamp size and may prove to be a valuable alternative in the treatment of long-bone fractures in very small animals.…”
Section: Introductionmentioning
confidence: 99%